Software Tool for Work and Occupational Radon Health Risk Modeling - Nikolić, Mladen; Deljanin, Milena; Sibinović, Predrag; Golubović, Dragan; Stevović, Svetlana (International Journal of Industrial Engineering and Management, 2018)
The occupational and work health effects of exposure to radon have been exhamined for many years. Recent advances have been made in evaluating the risk associated with radon exposure and in implementing remediation programs in dwellings. This research presents the development of a user friendly web based software package based upon current information on radonepidemiology, radon dosimetry, exhalation rates, long term measurements, demography, and countermeasure efficiency. The software has been designed to perform lung cancer risk calculations specific to populations for various exposure profiles and to evaluate, in terms of risk reduction, the efficiency of various countermeasures in dwellings. This paper presents an overview of the general structure of the software and outlines its most important modeling approaches. Radon mapping and modeling application is a web based application developed for purpose of occupational and residential health risk modeling. Its developed as web application to be available to students and scientist in Serbia. Also it have mission to collect data in unique data base. This data base will be a great resource in future research of radon. From software engineering point of view it’s based on PHP –Mysql platform for managing data in data base and Ajax for user interface. Article history: Received (02.10.2017); Revised (26.10.2017); Accepted (09.11.2017)